Genetic environment of the transferable oxazolidinone/phenicol resistance gene optrA in Enterococcus faecalis isolates of human and animal origin. (21st February 2016) - He, Tao; Shen, Yingbo; Schwarz, Stefan; Cai, Jiachang; Lv, Yuan; Li, Jun; Feßler, Andrea T.; Zhang, Rong; Wu, Congming; Shen, Jianzhong; Wang, Yang
Abstract : IS 1216E elements may play a role in disseminating antimicrobial resistance between Enterococcus faecalis of human and animal origin as the oxazolidinone/phenicol gene optrA and other resistance genes are located on the same conjugative plasmids. Abstract: Objectives: Aim of this study was to analyse 17 non-related Enterococcus faecalis isolates of human and animal origin for the genetic environment of the novel oxazolidinone/phenicol resistance gene optrA . Methods: WGS and de novo assembly were conducted to analyse the flanking sequences of the optrA gene in the 17 E. faecalis isolates. When optrA was located on a plasmid, conjugation assays were performed to check whether the plasmids are conjugative and to confirm the resistance phenotype associated with these plasmids. Results: All nine optrA- carrying plasmids were conjugated into E. faecalis JH2-2 and the transconjugants exhibited the optrA -associated phenotype. In these plasmids, an IS 1216E element was detected either upstream and/or downstream of the optrA gene. In eight plasmids, the phenicol exporter gene fexA was found upstream of optrA and in six plasmids, a novel erm (A)-related gene for macrolide–lincosamide–streptogramin B resistance was detected downstream of optrA . When located in the chromosomal DNA, the optrA gene was found downstream of the transcriptional regulator gene araC in four isolates, or downstream of the fexA gene in another four isolates. Integration of the optrA region into a Tn 558 -Tn 554 hybrid, located in the chromosomal radC gene, was seen in two isolates. Conclusions: The findings of the present study extend the current knowledge about the genetic environment of optrA and suggest that IS 1216E elements play an important role in the dissemination of optrA among different types of enterococcal plasmids. The mechanism underlying the integration of optrA into the chromosomal DNA requires further investigation.